The risk of trading mastering the most important element in financial speculation - Toma, Michael 1966- (Wiley trading series, 2012)
"Develop the skills to manage risk in the high-stakes world of financial speculation. The Risk of Trading is a practical resource that takes an in-depth look at one of the most challenging factors of trading--risk management. The book puts a magnifying glass on the issue of risk, something that every trader needs to understand in order to be successful.Most traders look at risk in terms of a "stop-loss" that enables them to exit a losing trade quickly. In The Risk of Trading, Michael Toma explains that risk is ever-present in every aspect of trading and advocates that traders adopt a more comprehensive view of risk that encompasses the strategic trading plan, account size, drawdowns, maximum possible losses, psychological capital, and crisis management. Shows how to conduct a detailed statistical analysis of an individual's trading methodology through back-testing and real-time results so as to identify when the methodology may be breaking down in actual trading Reveals why traders should think of themselves as project managers who are strategically managing risk The book is based on the author's unique 'focus on the risk' approach to trading using data-driven risk statistical analytics Using this book as a guide, trades can operate more as business managers and learn how to avoid market-busting losses while achieving consistently good results"--